A Modified Solvent Method for Preparation of Solid Dispersions: Preparation of solid dispersions - Sanjay J. Kshirsagar,; Anand Ubhe,; Jasmine Malshe,; Vidula Sengaokar, (Iranian Journal of Pharmaceutical Sciences, 2012)
The first aim of the present investigation was to prepare solid dispersions to improve the dissolution properties of oxcarbazepine and quetiapine using PEG 6000 as a carrier with the help of two methods of preparations viz. spray drying and modified solvent method, and to compare the two methods. The second objective was to apply the modified solvent method for preparation of sustained release solid dispersions of domperidone with Eudragit RLPO as a carrier. The solid dispersions of oxcarbazepine and quetiapine were prepared using spray drying and a modified solvent evaporation method. The modified method was then used to prepare solid dispersion of domperidone. All the preparations were evaluated for solubility and dissolution. The characterization was done using FTIR, PXRD and DSC. The solubility and dissolution rates increased significantly for oxcarbazepine and quetiapine in the solid dispersion with PEG 6000. The release of domperidone was decreased in the solid dispersion with Eudragit RLPO. The solubility and dissolution rates of oxcarbazepine and quetiapine were increased significanly in the solid dispersions prepared by both spray drying and modified solvent method. There was no significant difference in the release profiles of solid dispersion prepared by the two methods. The modified solvent method was effectively used for preparing sustained release solid dispersion of domperidone.